2011
DOI: 10.1186/1556-276x-6-545
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic band structure of PCBM by electron irradiation

Abstract: Tuning the electronic band structures such as band-edge position and bandgap of organic semiconductors is crucial to maximize the performance of organic photovoltaic devices. We present a simple yet effective electron irradiation approach to tune the band structure of [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) that is the most widely used organic acceptor material. We have found that the lowest unoccupied molecular orbital (LUMO) level of PCBM up-shifts toward the vacuum energy level, while the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 34 publications
3
41
1
Order By: Relevance
“…On the other hand, the most evident change is seen in the reduction prole where naphthalimide extends the one-electron double reduction of phthalimide to a reversible triple reduction. Not dissimilar to PC 61 BM, 70 this suggests that S2 has the capability to reversibly accept more than just one electron, benecial for its role in separating charge in a photovoltaic cell.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…On the other hand, the most evident change is seen in the reduction prole where naphthalimide extends the one-electron double reduction of phthalimide to a reversible triple reduction. Not dissimilar to PC 61 BM, 70 this suggests that S2 has the capability to reversibly accept more than just one electron, benecial for its role in separating charge in a photovoltaic cell.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…Since most good OSCs that are used as n-type materials like [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) and N2200 have a lowest unoccupied molecular orbital (LUMO) around −4.0 eV, [7,8] it is very difficult to realize a stable dopant with a HOMO above −4.0 eV as would be required for efficient electron transfer. Fortunately, Wei et al have reported a promising material, (4-(1,3-dimethyl-2,3-dihydro-1H-benzoimidazol-2-yl)phenyl) dimethylamine (N-DMBI), that can be used as stable n-type dopant due to a two-step thermally activated doping mechanism.…”
mentioning
confidence: 99%
“…The defect induced D band and G band appear at 1359 and 1586 cm -1 respectively in mGO. PCBM shows several Raman active vibration modes which basically originate from icosahedral symmetry of C 60 with the strongest peak at 1464±2 cm -1 for Ag(2) mode [29,30]. PCBGO shows D band and G band of graphene at 1358, and 1587 cm -1 respectively along with fullerene Ag(2) mode vibration band at 1460 cm -1 (inset, figure 5).…”
Section: Results and Dissuasionmentioning
confidence: 95%